Application of Discrete and Continuous Wavelets for Saudi Arabian Meteorological Data Analysis - Rehman, Shafiqur (2020)
This paper presents the wavelet-based analysis of meteorological parameters for nine meteorological stations in Saudi Arabia. The study utilised the daily mean values of pressure, temperature, relative humidity and wind speed data over a period of 16 years between 1990 and 2005. In case of rainfall data, daily total values were used. The time series of meteorological parameters has so much noise that their overall shape is not visible upon visual inspection. It has been observed in the present investigation that trends become more and more readable at decomposition at different scales. The wavelet tools have been used to reveal the trends of the meteorological data time series. If the signal itself includes sharp changes then successive approximation look less and less similar to the original signal. This paper deals with the meteorological data visualisation. such as pressure, temperature, relative humidity, rainfall and the wind speed time series of the Kingdom of Saudi Arabia. The present analysis is based on discrete and continuous wavelet transforms.